Human Astrovirus and Cryptosporidium Co-infection among Children with Gastroenteritis in Diyala Governorate - I Naif, Amal; A Hussein, Areej; J Shaker , Mohammed; A Hussein , Rawaa (Diyala Journal of Medicine, 2020)
Background: Gastroenteritis is the second leading cause of death in children under five years old. The highest mortality from diarrheal diseases in children lived crowded areas were poor sanitary and hygienic conditions found. Objective: To determine the co-infections between human astrovirus and Cryptosporidium spp. among children with gastroenteritis below 5 years of age in the Diyala governorate. Patients and Methods: A cross-sectional study was carried out for 100 patients with acute gastroenteritis who attended the Emergency Department of Pediatrics in Al-Batool Teaching Hospital for Maternity and Pediatric in Baqubah city, during the period from July 2019 to February 2020. Real time-PCR was used to detect human astrovirus while enzyme- linked immunosorbent assay was used to detect Cryptosporidium spp. A specific formula sheet was used to collect demographic data such as age, gender, mother education, and type of milk feeding. Results: Out of 100 samples, 14 samples were positive for human astrovirus and 38 samples were positive for Cryptosporidium. The infection rate is more common in males (9 cases) (25cases) rather than females, and in age group less than years 11(78.58%) and 34(89.47%) respectively. Artificial feeding showed higher frequencies of infection than others in the study population. Co-infection astrovirus and Cryptosporidium found in four patients, all of whom were males aged under one-year and the difference was statistically significant with all parameters. Conclusion: A high proportion of positive cases for human astrovirus and Cryptosporidium spp. were notes in males and the age group less than one year’s co-infection showed high frequency in the study population.